Perceptions of Health Among Women Recovering from Sexual Violence. - Risisky, Deb (Distribution: Fall ; Public Health., 2014)
The sabbatical focus was a qualitative study with sexual assault survivors related to current health status.
Keywords: dept.pch; faculty_collection; sabbatical_report

Gearing up to GEAR UP: four perspectives on early implementation considerations for GEAR UP - Arafeh, Sousan; Fopiano, Joy; Risisky, Deb; Haynes, Norris M (Nera Conference Proceedings 2012, 2012)
Citation Key Alias: lens.org/016-608-465-938-91X
Keywords: dept.edl; dept.pch; ⛔ No DOI found

Promoting pro-social skills to reduce violence among urban middle school youth - Risisky, Deb; MacGregor, J; Smith, D. A.; Abraham, J; Archambault, M (Journal of Youth Development, 2019)
Adolescent violence is a significant public health problem. The goal of this evaluation was to determine whether communication skills, relationships with adults, and relationships with peers were enhanced through participating in an after-school program aimed at reducing violence-related behaviors among urban middle school youth. Elements that helped to foster success among our population were providing a program that enabled consistent choice in recreational activities in a safe place, and also providing busing home to increase safety. A non-experimental study was conducted with 115 students who participated in the program. Bivariate, ANOVA analysis, and Kruskal–Wallis tests were carried out. Results indicated that participating in the program significantly impacted student relationships with adults and their peers as well as positively impacted their communication skills. The program was designed with purposeful activities that would address pro-social behaviors, enhance youth interest, and increase attendance. The program specifically used recreation to help foster relationships with their peers and the adults in the program, with the intention of reducing conflict, and therefore violence among the students.
1 citations (Crossref) [2023-10-31]
Keywords: After-school program; Recreation programs; Youth violence; dept.pch; dept.rec; peer-reviewed

Examining Delivery Method and Infant Feeding Intentions between Women in Traditional and Non-Traditional Prenatal Care. - Risisky, Deb; Chan, Ronna L; Zigmont, Victoria A; Asghar, Syed Masood; DeGennaro, Nancy (Maternal and child health journal, 2018)
Introduction The purpose of the study is to evaluate delivery method and breastfeeding initiation in women enrolled in group prenatal care (CenteringPregnancy) and in traditional prenatal care. Methods Data were obtained from medical records of a hospital-based midwifery practice in south central Connecticut that offered both types of prenatal care programs. Medical information from 307 women enrolled in this practice was included in the analysis. Out of the 307, 80 were enrolled in group prenatal care. Socio-demographic, lifestyle, and previous and current obstetrical information from medical records formed the basis of comparison. Bivariate and logistic regression analyses were carried out. Results Women in Centering had fewer planned cesarean sections (1.3 vs. 12.8%) and had a higher breastfeeding initiation (88.7 vs. 80.0%). However, Centering women were found to have a higher portion of unplanned cesarean sections (27.5 vs. 11.0%). Both the unadjusted and the adjusted odds ratios of having a cesarean planned delivery were lower in the group care. Women in Centering had 2.44 (95% CI 1.05, 5.66) times the odds of breastfeeding initiation compared to the odds for women in traditional prenatal care after adjusting for maternal age, smoking status, gestation and race. Discussion CenteringPregnancy can have positive impact for the woman and baby. This program implementation saw lower rates of elective cesarean sections and increased breastfeeding compared to women in traditional care.
7 citations (Crossref) [2023-10-31] Place: United States Risisky, Deb. Department of Public Health, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06514, USA. risiskyd1@southernct.edu. Chan, Ronna L. Department of Epidemiology, Gillings School of Global Public Health, The University of North Carolina at Chapel Hill, Chapel Hill, NC, USA. Zigmont, Victoria A. Department of Public Health, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06514, USA. Asghar, Syed Masood. Connecticut Department of Mental Health and Addiction Services, Hartford, CT, USA. DeGennaro, Nancy. Center for Women's Health and Midwifery, Yale-New Haven Hospital, Hospital of Saint Raphael Campus, New Haven, CT, USA.
Keywords: *Breast Feeding/px [Psychology]; *Breast Feeding/sn [Statistics & Numerical Data]; *Cesarean Section/sn [Statistics & Numerical Data]; *Intention; *Mothers; *Prenatal Care/mt [Methods]; Adult; Breast Feeding; Breastfeeding; CenteringPregnancy; Cesarean Section; Cesarean section; Connecticut; Female; Group Processes; Humans; Infant; Infant; Newborn; Intention; Mothers; Mothers/px [Psychology]; Mothers/sn [Statistics & Numerical Data]; Pregnancy; Prenatal Care; Prenatal care; Standard of Care; adult; behavior; breast feeding; cesarean section; comparative study; dept.pch; female; group process; health care quality; human; infant; mother; newborn; peer-reviewed; pregnancy; prenatal care; procedures; psychology; statistics and numerical data